Analisis Hubungan Linier Berganda Antara Integritas dan Kompetensi Terhadap Peningkatan Profesionalitas Widyaiswara - Diki Sadikin; Abdur Rahim; Alriyono (JURNAL PENDIDIKAN DAN PELATIHAN PERTAHANAN, 2024)
Integrity and competence are two main pillars that complement each other in improving the professionalism of the Jemenhan Defense Education and Training Center Widyaiswara.  High integrity is reflected in honesty, steadfast principles, and high dedication to duty. This is the basis for Widyaiswara to provide quality education and training.  Meanwhile, adequate competency includes mastery of knowledge, skills and experience relevant to the field of defense management. By combining the two, Widyaiswara is able to become an inspiring role model, produce quality graduates, and contribute to improving the quality of human resources in the defense sector. In this research, researchers analyzed the extent to which integrity and competence jointly influence the level of professionalism of Widyaiswara at the Jemenhan Education and Training Center.  This research adopts quantitative methods with probability sampling techniques. A total of 68 Widyaiswara and students at the Jemenhan Education and Training Center were randomly selected as respondents to test the hypothesis regarding the influence of integrity and competence together on the professionalism of Widyaiswara.  Based on the results of the analysis, integrity and competence are proven to be key factors that synergistically increase the professionalism of the Jemenhan Defense Education and Training Center Widyaiswara. The results of the multiple linear regression test showed that the regression line equation Y = 22.857 + 0.259 X1 + 0.217 together with the professionalism of the Jemenhan Education and Training Center Widyaiswara was positive at 64.9%.